2014
DOI: 10.1016/j.molonc.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The tumor promoting activity of the EP4 receptor for prostaglandin E2 in murine skin

Abstract: Pharmacological and genetic approaches have shown that prostaglandins (PGs) synthesized by cyclooxygenase-2 (COX-2) have tumor promoting/progression activity in murine skin. To determine whether the EP4 receptor for PGE2 contributes to this tumor promoting/progression activity, EP4 over-expressing mice (BK5.EP4) were generated and subjected to several carcinogenesis protocols. A two-stage 7,12-dimethylbenz[a]anthracene (DMBA)-12-O-tetradecanoylphorbol- 13-acetate (TPA) protocol resulted in 25-fold more squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
(107 reference statements)
0
13
0
Order By: Relevance
“…EP4 receptor signaling attenuates brain inflammation [18] and exerts inhibitory effects on LPS-induced NFκB signaling [30]. However, EP4 activation promotes LPS-induced IL-23 secretion in immature dendritic cells and IL-17 production in activated T cells [31], and exerts pro-tumorigenic actions [32]. Therefore, modulation of EP4 activation in vivo can potentially exert benefits by attenuating the degree of innate immune responses in naïve microglia, but its various actions in different cell types could be detrimental or beneficial depending on the type and stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…EP4 receptor signaling attenuates brain inflammation [18] and exerts inhibitory effects on LPS-induced NFκB signaling [30]. However, EP4 activation promotes LPS-induced IL-23 secretion in immature dendritic cells and IL-17 production in activated T cells [31], and exerts pro-tumorigenic actions [32]. Therefore, modulation of EP4 activation in vivo can potentially exert benefits by attenuating the degree of innate immune responses in naïve microglia, but its various actions in different cell types could be detrimental or beneficial depending on the type and stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin E 2 is known to bind and activate its G protein-coupled receptors, prostaglandin E 2 receptors 1 to 4 (known as EP 1 , EP 2 , EP 3, and EP 4 ). The tumor-promoting role of Cox-2 can partly work through each EP receptor, and inhibition of the receptor pathways has the potential to prevent cutaneous SCCs [52][53][54][55] . For example, Tober et al reported suppressed UV-induced skin tumor formation by treatment with the specific EP 1 antagonist ONO-8713 52 .…”
Section: The Role Of Cox-2 In Stem Cell-originating Cutaneous Tumor Fmentioning
confidence: 99%
“…Several studies in murine models have demonstrated the importance of COX-1, COX-2, PGE 2 , and PGE 2 receptors for skin tumor development and growth (Fischer, Pavone, Mikulec, Langenbach, & Rundhaug, 2007;Morita, 2002;Simper et al, 2014;Sung, He, Hwang, & Fischer, 2006;Tiano et al, 2002;Tober et al, 2006;Zelenay et al, 2015). Targeted disruptions of the genes encoding either COX-1 or COX-2 led to altered epidermal keratinocyte differentiation and reduced skin tumorigenesis in a multistage mouse skin model (Tiano et al, 2002).…”
Section: Role Of Cox-2 and Scc Tumorigenesismentioning
confidence: 99%